Flexible composite material and method for producing the same

CN119319598BActive Publication Date: 2026-10-27INST OF WOOD INDUDTRY CHINESE ACAD OF FORESTRY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410472525.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-19
Publication Date
2026-10-27
Estimated Expiration
2044-04-19

AI Technical Summary

Technical Problem

[0003]此外,竹材本身纵向柔韧性优异,但是横向易开裂,抗拉强度低,目前改善竹皮常用方法是在竹皮刨切后即刻贴上无纺布进行固定,可改善其开裂行为

Benefits of technology

[0024]本发明的柔性复合材料不会开裂,具有优异的柔韧性,且力学性能优异。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119319598B_ABST
    Figure CN119319598B_ABST
Patent Text Reader

Abstract

The present application provides a kind of flexible composite material and its preparation method.The flexible composite material includes: matrix, the matrix is derived from wood material or bamboo material;And, biomass fiber film, the biomass fiber film exists in at least one surface of the matrix;And, the matrix with the biomass fiber film has elastomer material, at least part of the elastomer material penetrates into the pore of the matrix.The flexible composite material of the present application does not crack, has excellent flexibility, and excellent mechanical properties.The preparation method of the flexible composite material of the present application is simple and easy to operate, raw materials are easy to obtain, and is suitable for mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a flexible composite material and its preparation method, and particularly to a flexible composite material based on bamboo or wood materials and its preparation method, belonging to the field of wood materials. Background Technology

[0002] Thinly sliced ​​bamboo veneer (hereinafter referred to as bamboo veneer), as a new type of decorative veneer material with natural bamboo texture, is now in industrial production and product application. Bamboo veneer is made from bamboo strips as raw material, processed through a series of steps including square lamination, softening and slicing, and backing reinforcement to produce large-format thin bamboo strips. While retaining the natural texture and color of bamboo, bamboo veneer also embodies the humanistic sentiment and low-carbon environmental protection concept of bamboo in traditional culture, possessing both aesthetic, cultural, and green contemporary attributes.

[0003] In addition, bamboo itself has excellent longitudinal flexibility, but it is prone to cracking in the transverse direction and has low tensile strength. Currently, the common method to improve bamboo veneer is to immediately attach non-woven fabric after slicing the bamboo veneer for fixation, which can improve its cracking behavior. However, because non-woven fabric affects the aesthetics of the bamboo surface, and its opacity obscures the unique texture of the bamboo, it can only be used as a backing material. Bamboo veneer surfaces without non-woven fabric still struggle to overcome the cracking problem. Summary of the Invention

[0004] The problem the invention aims to solve

[0005] In view of the technical problems existing in the prior art, the present invention first provides a flexible composite material. The flexible composite material of the present invention does not crack, has excellent flexibility, and excellent mechanical properties.

[0006] The present invention also provides a method for preparing flexible composite materials, which is simple and easy to implement, uses readily available raw materials, and is suitable for mass production.

[0007] Solution for solving the problem

[0008] This invention first provides a flexible composite material, comprising:

[0009] The matrix, said matrix being derived from wood or bamboo materials; and,

[0010] A biomass fiber membrane, said biomass fiber membrane being present on at least one surface of the substrate; and...

[0011] An elastomer material is present between the substrate and the biomass fiber membrane, and at least a portion of the elastomer material permeates into the pores of the substrate.

[0012] According to the flexible composite material of the present invention, the thickness of the matrix is ​​0.1-0.6 mm, preferably 0.15-0.25 mm; and / or,

[0013] The biomass fiber membrane has a thickness of less than 0.1 mm, preferably 0.04-0.06 mm, and a density of 0.5 g / cm³. 3 The preferred values ​​are 0.34-0.37 g / cm³. 3 .

[0014] According to the flexible composite material of the present invention, the pores of the biomass fiber membrane are permeated with an elastomer material; preferably, the biomass fiber membrane is derived from lignocellulosic cells and / or bamboo fiber cells; more preferably, the biomass fiber membrane is obtained by papermaking using a papermaking screen.

[0015] According to the flexible composite material of the present invention, the elastomer material comprises aqueous polyurethane.

[0016] The present invention also provides a method for preparing a flexible composite material according to the present invention, which includes: using an elastomer solution to composite a matrix with a biomass fiber membrane to obtain a molded body.

[0017] According to the preparation method of the present invention, the preparation method of the biomass fiber membrane includes: dispersing biomass fibers in a solvent to obtain a slurry; and forming the slurry into a paper using a papermaking screen to obtain a biomass fiber membrane.

[0018] According to the preparation method of the present invention, the mass concentration of the biomass fiber in the slurry is 0.05%-0.2%, preferably 0.05%-0.1%.

[0019] According to the preparation method of the present invention, the dispersion treatment includes dispersion treatment using a mixer; preferably, the rotation speed of the mixer is 15000-20000 rpm, and the dispersion treatment time is 1h to 2h.

[0020] According to the preparation method of the present invention, the solid content of the elastomer solution is 28-34%; and / or,

[0021] An elastomer solution is applied to cause the substrate to adhere to the biomass fiber membrane; the application method includes one or more combinations of spreading, coating, casting and spraying.

[0022] According to the preparation method of the present invention, the preparation method further includes a step of curing the molded body; preferably, the curing temperature is 70-90°C, the curing time is 5-8 minutes, and the curing pressure is 0.5-2 MPa.

[0023] The effects of the invention

[0024] The flexible composite material of the present invention does not crack, has excellent flexibility, and excellent mechanical properties.

[0025] The preparation method of the flexible composite material of the present invention is simple and easy to implement, the raw materials are readily available, and it is suitable for mass production. Attached Figure Description

[0026] Figure 1 The surface and cross-sectional morphologies of the flexible composite materials of Examples 1-3 of the present invention and the conventional composite material of Comparative Example 1 are shown.

[0027] Figure 2 The surface morphology of the flexible composite materials of Examples 1-3 of the present invention and the conventional composite material of Comparative Example 1 are shown at 100x magnification (top) and 200x magnification (bottom) after testing the transverse tensile strength. Detailed Implementation

[0028] Various exemplary embodiments, features, and aspects of the present invention will be described in detail below. The term "exemplary" as used herein means "serving as an example, embodiment, or illustration." Any embodiment described herein as "exemplary" is not necessarily to be construed as superior to or better than other embodiments.

[0029] Furthermore, to better illustrate the present invention, numerous specific details are set forth in the following detailed embodiments. Those skilled in the art should understand that the present invention can be practiced without certain specific details. In other instances, methods, means, apparatus, and steps well known to those skilled in the art have not been described in detail in order to highlight the spirit of the present invention.

[0030] Unless otherwise stated, all units used in this specification are international standard units, and all numerical values ​​and ranges appearing in this invention should be understood to include systematic errors that are unavoidable in industrial production.

[0031] In this specification, the word "may" has two meanings: to perform a certain process and not to perform a certain process.

[0032] In this specification, references to "some specific / preferred embodiments," "other specific / preferred embodiments," "implementation," etc., refer to specific elements (e.g., features, structures, properties, and / or characteristics) related to that embodiment, which are included in at least one of the embodiments described herein and may or may not be present in other embodiments. Furthermore, it should be understood that these elements may be combined in any suitable manner in various embodiments.

[0033] In this specification, the range of values ​​referred to as "value A to value B" refers to the range including the endpoint values ​​A and B.

[0034] In this instruction manual, when "room temperature" or "room temperature" is used, the temperature can be 15-25℃.

[0035] <First Aspect>

[0036] A first aspect of the present invention provides a flexible composite material comprising:

[0037] The matrix, said matrix being derived from wood or bamboo materials; and,

[0038] A biomass fiber membrane, said biomass fiber membrane being present on at least one surface of the substrate; and...

[0039] An elastomer material is present between the substrate and the biomass fiber membrane, and at least a portion of the elastomer material permeates into the pores of the substrate.

[0040] The flexible composite material of the present invention does not crack, has excellent flexibility, and excellent mechanical properties.

[0041] In this invention, the matrix is ​​derived from wood or bamboo materials, preferably from bamboo veneer. The bamboo veneer includes common natural and carbonized side-pressed sliced ​​bamboo veneer, flat-pressed sliced ​​bamboo veneer, or other bamboo veneers prepared from bamboo engineered wood as the slicing raw material. The bamboo veneer can also be replaced by rotary-cut bamboo veneer, sliced ​​reconstituted wood veneer, sliced ​​reconstituted bamboo veneer, sliced ​​wood veneer, or rotary-cut wood veneer, etc.; the rotary-cut bamboo veneer is a bamboo veneer material prepared from bamboo as raw material using rotary cutting technology; the sliced ​​reconstituted wood veneer is a reconstituted wood veneer material prepared from reconstituted wood as raw material using softening slicing technology; the sliced ​​reconstituted bamboo veneer is a reconstituted bamboo veneer material prepared from reconstituted bamboo as raw material using softening slicing technology; the rotary-cut wood veneer is a wood veneer material prepared from the xylem obtained from trees using softening slicing technology; the rotary-cut wood veneer is a wood veneer material prepared using rotary cutting technology.

[0042] In some specific implementations, the thickness of the substrate is 0.1-0.6 mm, preferably 0.15-0.25 mm, for example: 0.12 mm, 0.16 mm, 0.18 mm, 0.2 mm, 0.22 mm, 0.24 mm, 0.3 mm, 0.35 mm, 0.4 mm, 0.45 mm, 0.5 mm, 0.55 mm, etc.

[0043] The biomass fiber membrane of the present invention is present on at least one surface of the substrate. In this invention, the easily cracked and broken bamboo surface is repaired by bridging with biomass fibers and enhanced with the flexibility of an elastomer material. By using the biomass fiber membrane, the present invention increases the lateral connection structure between bamboo fibers, thus hindering cracking behavior between lateral tissues. Specifically, in this invention, the elastomer material includes, but is not limited to, elastomer resin materials such as waterborne polyurethane.

[0044] Specifically, in this invention, the biomass fiber membrane is derived from lignocellulosic cells and / or bamboo fiber cells; the biomass fiber membrane of this invention uses wood or bamboo fiber cells as its main component. Specifically, the biomass fiber membrane of this invention can be derived from fibers formed from lignocellulosic materials or bamboo materials. For lignocellulosic materials, it can be the trunk or roots of various trees, preferably using the heartwood from the trunk. For bamboo materials, it can be various types of bamboo, including scattered, clumping, and mixed-growth types, such as green bamboo, yellow bamboo, purple bamboo, black bamboo, spotted bamboo, bitter bamboo, sweet bamboo, cinnamon bamboo, dragon bamboo, square bamboo, and moso bamboo. Furthermore, the biomass fiber membrane of this invention can be derived from pulp fibers.

[0045] In some specific embodiments, the biomass fiber membrane of the present invention has a relatively thin thickness, approximately 0.1 mm or less, preferably 0.04-0.06 mm, for example: 0.01 mm, 0.02 mm, 0.03 mm, 0.04 mm, 0.05 mm, 0.06 mm, 0.07 mm, etc.; and the biomass fiber membrane of the present invention also has a low density, approximately 0.5 g / cm³. 3 The preferred values ​​are 0.34-0.37 g / cm³. 3 For example, 0.1 g / cm³ 3 0.2g / cm 3 0.3g / cm 3 0.32g / cm 3 0.33g / cm 3 0.35g / cm 3 0.36g / cm 3 0.38 g / cm 3 0.4g / cm 3 wait.

[0046] Preferably, the biomass fiber membrane is obtained by papermaking using a papermaking screen. Biomass fiber membranes obtained by papermaking using a papermaking screen are thinner and have a more suitable density, which is beneficial for obtaining flexible composite materials.

[0047] In this invention, an elastomer material is present between the matrix and the biomass fiber membrane, and at least a portion of the elastomer material permeates into the pores of the matrix. By allowing the elastomer material to permeate into the pores of the matrix, the flexibility of the bamboo material can be significantly increased.

[0048] This invention utilizes an elastomer material, preferably waterborne polyurethane with good compatibility and elasticity with bamboo, to fill and encapsulate the cracks and pores in the bamboo itself and those generated during the slicing process at multiple scales, increasing the bamboo's flexibility and lateral strength. Furthermore, by layering the biomass fiber membrane and elastomer material, the two materials can be fused together, resulting in a more uniform distribution and better adhesion.

[0049] In some specific embodiments, an elastomer material is also permeated into the pores of the biomass fiber membrane; that is, an elastomer material is permeated into both the pores of the matrix and the pores of the biomass fiber membrane. By permeating the pores of the biomass fiber membrane with an elastomer material, the biomass fiber membrane and the elastomer material are fused together, resulting in superior adhesion.

[0050] Furthermore, the flexible composite material matrix of the present invention has a backing layer on the side away from the biomass fiber membrane, which further provides fixation and support for the matrix. Specifically, the backing layer can be a non-woven fabric.

[0051] In some specific implementations, elastomeric materials are also permeated into the pores of the backing layer. By permeating elastomeric materials into the pores of the backing layer, the stress dispersion of the flexible composite material can be further improved.

[0052] The resulting flexible composite material is a novel bamboo-based material with ultra-high flexibility. It can be used in flexible packaging, flexible substrates, and irregular decorative veneers, expanding the application range of bamboo skin, increasing product added value, and has great development potential.

[0053] <Second aspect>

[0054] A second aspect of the present invention provides a method for preparing the flexible composite material according to the first aspect of the present invention, comprising: using an elastomer solution to composite a matrix with a biomass fiber membrane to obtain a molded body. The preparation method of the present invention is simple and easy to implement, the raw materials are readily available, and it is suitable for mass production.

[0055] In some specific implementations, the preparation method of the biomass fiber membrane includes: dispersing biomass fibers in a solvent to obtain a slurry; and forming the slurry using a papermaking screen to obtain a biomass fiber membrane. The present invention obtains the biomass fiber membrane by using a papermaking screen, and the fiber content and the thickness of the fiber membrane can be controlled according to the actual application scenario.

[0056] Specifically, the biomass fiber concentration in the pulp is 0.05%-0.2%, preferably 0.05%-0.1%, for example: 0.06%, 0.07%, 0.08%, 0.09%, 0.11%, 0.13%, 0.15%, 0.17%, 0.19%, etc. The mesh size of the papermaking screen can be 60-120 mesh, for example: 70 mesh, 80 mesh, 90 mesh, 100 mesh, 110 mesh, etc.

[0057] In some specific implementations, the dispersion treatment includes dispersion using a mixer; preferably, the mixer speed is 15,000-20,000 rpm, for example: 16,000 rpm, 17,000 rpm, 18,000 rpm, 19,000 rpm, etc.; the dispersion treatment time is 1 hour to 2 hours, for example: 1.2 hours, 1.4 hours, 1.6 hours, 1.8 hours, etc. Dispersion treatment can make the biomass fibers more uniform, which is beneficial for the formation of biomass fiber membranes.

[0058] Furthermore, the solid content of the elastomer solution is 28-34%, for example: 29%, 30%, 31%, 32%, 33%, etc.; and / or, the matrix is ​​adhered to the biomass fiber membrane by applying the elastomer solution; the application method includes one or more combinations of spreading, coating, casting and spraying.

[0059] Specifically, this invention does not impose particular limitations on the timing of applying the elastomer solution; it can be set as needed, as long as the elastomer solution is present between the flexible composite matrix and the biomass fiber membrane. Specifically, the elastomer solution can be applied first to one side of the matrix, and then the biomass fiber membrane can be assembled onto the side of the matrix with the elastomer solution. Alternatively, the elastomer solution can be applied after the biomass fiber membrane has been assembled onto one side of the matrix. Another option is to apply the elastomer solution first to one side of the matrix, and then assemble the biomass fiber membrane onto that side. To facilitate more uniform penetration of the elastomer solution into the pores of the matrix and the biomass fiber membrane, the elastomer solution can then be applied again to the side of the biomass fiber membrane furthest from the elastomer solution.

[0060] The present invention does not impose a particular limitation on the amount of elastomer solution used, and it can be set as needed, as long as the function of the present invention can be achieved. Specifically, the amount of elastomer solution used each time can be 5-15 g / m³. 2 Preferred concentration: 8-10 g / m 2 For example: 5.5g / m 2 6g / m 2 6.5g / m 2 7g / m 2 7.5g / m 2 8g / m 2 8.5g / m 2 9g / m 2 9.5g / m 2 10g / m 2 10.5g / m 2 11g / m 2 11.5g / m 2 12g / m 2 13g / m 2 14g / m 2 wait.

[0061] Furthermore, a backing layer can be provided on the side of the flexible composite material matrix of the present invention away from the biomass fiber membrane, thereby further fixing and supporting the matrix. Specifically, the backing layer can be a non-woven fabric.

[0062] Furthermore, the backing layer can be assembled onto one side of the substrate first, followed by the assembly of the biomass fiber membrane, or the biomass fiber membrane can be assembled onto one side of the substrate first, followed by the assembly of the backing layer. Specifically, an adhesive can be used to assemble the backing layer onto one side of the substrate. The amount of adhesive used is not particularly limited in this invention and can be selected as needed.

[0063] Furthermore, after the backing layer is assembled on one side of the substrate, hot pressing can be performed to make the backing layer and the substrate tightly bonded together. Specifically, the hot pressing temperature can be 70-110℃, such as 80℃, 90℃, 100℃, etc.; the hot pressing time can be 50-100 seconds, such as 60 seconds, 70 seconds, 80 seconds, 90 seconds, etc.

[0064] The present invention does not impose any particular limitation on the adhesive, as long as it can assemble the backing layer onto one side of the substrate, such as commercially available solid powder adhesives.

[0065] In some specific embodiments, the preparation method further includes a step of curing the molded body; preferably, the curing temperature is 70-90℃, for example: 750℃, 80℃, 85℃, etc.; the curing time is 5-8 minutes, for example: 5.5 minutes, 6 minutes, 6.5 minutes, 7 minutes, 7.5 minutes, etc.; the curing pressure is 0.5-2MPa, for example: 0.7MPa, 0.9MPa, 1.1MPa, 1.3MPa, 1.5MPa, 1.7MPa, 1.9MPa, etc.

[0066] Finally, the cured product can be polished to obtain the flexible composite material of the present invention.

[0067] Example

[0068] The embodiments of the present invention will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer are followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0069] In this example, the waterborne polyurethane used is model 1926, manufactured by Yoshida Chemical Co., Ltd. It has a solid content of approximately 34%, a pH value of 6-8, and a viscosity of less than 350 mPa·s.

[0070] Example 1

[0071] (1) Non-woven fabric was applied to one side of the sliced ​​bamboo veneer. The adhesive used was a commercially available three-component solid powder adhesive. The hot pressing temperature was 90℃ and the hot pressing time was 80 seconds. The final thickness was 0.15mm.

[0072] (2) Pulp fibers were prepared at a mass concentration of 0.1% to obtain an aqueous pulp. The pulp fibers in the aqueous pulp were dispersed using a mixer at a speed of 15,000 rpm for 2 hours. Then, papermaking was carried out using a papermaking screen with a mesh size of 80 mesh to obtain a pulp fiber membrane for later use.

[0073] (3) Inject the water-based polyurethane solution into a high-pressure spray gun and spray it onto the side of the sliced ​​bamboo veneer that was not covered with non-woven fabric in step 1). Spray once, with an application rate of 10 g / m². 2 The solid content of polyurethane in waterborne polyurethane is 34%.

[0074] (4) Assemble the pulp fiber membrane from (2) onto the side of the sliced ​​bamboo skin in (3) that has water-based polyurethane, and then spray it with water-based polyurethane. The spraying is done once, and the amount of adhesive applied is 10g / m².2 The solid content of polyurethane in the waterborne polyurethane is 34%, and a molded body is obtained, wherein the waterborne polyurethane penetrates at least into the pores of the pulp fiber membrane, the sliced ​​bamboo skin and the nonwoven fabric.

[0075] (5) Place the molded body from (4) into a press for heating and pressure curing at a temperature of 80°C for 8 minutes and a pressure of 2MPa.

[0076] (6) Polish the surface of the cured and dried bamboo skin to obtain a flexible composite material.

[0077] Example 2

[0078] (1) Non-woven fabric was applied to one side of the sliced ​​bamboo veneer. The adhesive used was a commercially available three-component solid powder adhesive. The hot-pressing temperature was 90℃ and the hot-pressing time was 80 seconds. The final thickness was 0.15mm.

[0079] (2) Pulp fibers were prepared at a mass concentration of 0.1% to obtain an aqueous pulp. The pulp fibers in the aqueous pulp were dispersed using a mixer at a speed of 15000 rpm for 2 hours. Papermaking was carried out using a papermaking screen with a mesh size of 80 mesh to obtain a pulp fiber membrane for later use.

[0080] (3) Inject the water-based polyurethane solution into a high-pressure spray gun and spray it onto the side of the sliced ​​bamboo veneer that was not covered with non-woven fabric in step 1). Spray once, with an application rate of 10 g / m². 2 The solid content of polyurethane in waterborne polyurethane is 34%.

[0081] (4) Assemble the pulp fiber membrane in (2) onto the side of the sliced ​​bamboo skin in (3) with water-based polyurethane to obtain a molded body, and at least the water-based polyurethane penetrates into the pores of the pulp fiber membrane and the sliced ​​bamboo skin.

[0082] (5) Place the molded body from (4) into a press for heating and pressure curing at a temperature of 80°C for 8 minutes and a pressure of 2MPa.

[0083] (6) Polish the surface of the cured and dried bamboo skin to obtain a flexible composite material.

[0084] Example 3

[0085] (1) Non-woven fabric was applied to one side of the sliced ​​bamboo veneer. The adhesive used was a commercially available three-component solid powder adhesive. The hot-pressing temperature was 90℃ and the hot-pressing time was 80 seconds. The final thickness was 0.15mm.

[0086] (2) Prepare an aqueous pulp by mixing pulp fibers at a mass concentration of 0.1% pulp fibers. Use a mixer to disperse the pulp fibers in the aqueous pulp. The mixing speed is 15000 rpm and the time is 2 hours. Use a papermaking screen to make paper. The mesh size of the papermaking screen is 80 mesh. Prepare a pulp fiber membrane for later use.

[0087] (3) Assemble the pulp fiber membrane from (2) onto the side of the sliced ​​bamboo skin from (1) that is not covered with nonwoven fabric.

[0088] (4) Inject the water-based polyurethane solution into the high-pressure spray gun and spray it onto the side of the sliced ​​bamboo skin with the pulp fiber membrane in (3). The spraying is done once, and the amount of adhesive applied is 10g / m². 2 The solid content of polyurethane in the waterborne polyurethane is in the range of 34%, and a molded body is obtained, wherein at least the waterborne polyurethane penetrates into the pores of the pulp fiber membrane and the sliced ​​bamboo skin.

[0089] (5) Place the molded body from (4) into a press for heating and pressure curing at a temperature of 80°C for 8 minutes and a pressure of 2MPa.

[0090] (6) Polish the surface of the cured and dried bamboo skin to obtain a flexible composite material.

[0091] Comparative Example 1

[0092] One side of the sliced ​​bamboo veneer is laminated with non-woven fabric using a three-component solid powder adhesive. The hot-pressing temperature is 90℃, and the hot-pressing time is 80 seconds. The final product is processed to a thickness of 0.15mm, resulting in a traditional composite material.

[0093] Performance testing

[0094] 1. Flexibility

[0095] The flexibility of the three examples compared to untreated bamboo skin was tested by winding steel pipes with diameters of 50mm, 30mm, 14mm, 13mm, 12mm, 11mm, 10mm, 9mm, 8mm, 7mm, 6mm, 5mm, 4mm, 3mm, 2mm, 1mm, and 0.5mm, with the standard that no breakage occurred during winding. The results are shown in Table 1.

[0096] 2. Transverse tensile strength

[0097] The transverse tensile strength of the three embodiments and the untreated bamboo skin was tested using a mechanical testing machine. All results are shown in Table 1.

[0098] Table 1

[0099]

[0100] As shown in Table 1, the mechanical flexibility and mechanical properties of the flexible composite materials in the embodiments of the present invention are significantly improved compared with the comparative examples. All three embodiments can be wound around a 0.5 mm thick steel pipe without breaking. The transverse tensile strength of the flexible composite materials in the embodiments of the present invention is also significantly improved, with increases of 88.66%, 19.57%, and 40.11% respectively compared to untreated bamboo veneer in Examples 1, 2, and 3.

[0101] 3. Transmission electron microscopy (TEM) testing

[0102] The surface and cross-sectional morphology of the flexible composite materials of Examples 1-3 and the conventional composite material of Comparative Example 1 were observed by transmission electron microscopy (TEM). The results are as follows: Figure 1 As shown.

[0103] Wherein, a represents the surface structure morphology of the conventional composite material in Comparative Example 1, and d, g, and j represent the surface structure morphologies of Examples 3, 2, and 1, respectively. It is evident from d, g, and j that the waterborne polyurethane has permeated into the pulp fiber membrane, while a does not contain waterborne polyurethane.

[0104] b represents the cross-sectional morphology of the traditional composite material in Comparative Example 1, while e, h, and k represent the cross-sectional morphologies of Examples 3, 2, and 1, respectively. As can be seen from e, h, and k, the waterborne polyurethane also penetrates into the pore structure of the bamboo, resulting in a tight bond between the pulp fiber membrane and the bamboo.

[0105] 4. Transmission electron microscopy microscopy test after lateral stretching

[0106] The surface and cross-sectional morphology of the flexible composite materials of Examples 1-3 and the conventional composite material of Comparative Example 1 after transverse stretching were observed by transmission electron microscopy (TEM). The results are as follows: Figure 2 As shown.

[0107] Depend on Figure 2 It can be seen that during the transverse stretching process, the pulp fiber membrane of Example 3 is more prone to falling off, so only a small amount of waterborne polyurethane plays a reinforcing role on the sliced ​​bamboo skin.

[0108] During the transverse stretching process, the pulp fiber membrane of Example 2 also detached when subjected to transverse stretching. This may be because the amount of water-based polyurethane spraying is too small, which cannot completely fill the pores and tightly bond the pulp fiber membrane and the sliced ​​bamboo skin. During stretching, it is easy to break at the weak bonding point of the pulp fiber membrane.

[0109] During the transverse stretching process, the complex structure formed by the interweaving and entanglement of the pulp fiber membrane in Example 1 disperses the stress from slicing the bamboo skin. At this time, a large number of pulp fibers are dispersed and pulled out, thereby preventing further expansion of cracks. At the same time, the water-based polyurethane permeated in the nonwoven fabric also has a certain stress-dispersing effect.

[0110] The various embodiments of the present invention have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments. The terminology used herein is chosen to best explain the principles, practical application, or technical improvements to the embodiments in the market, or to enable others skilled in the art to understand the embodiments disclosed herein.

Claims

1. A flexible composite material, characterized in that, include: The substrate is bamboo skin; as well as, A biomass fiber membrane, wherein the biomass fiber membrane is present on at least one surface of the substrate, the biomass fiber membrane is derived from bamboo fiber cells, and the biomass fiber membrane is obtained by papermaking using a papermaking screen; and, An elastomer material is present between the matrix and the biomass fiber membrane, and at least a portion of the elastomer material permeates into the pores of the matrix; The pores of the biomass fiber membrane are permeated with an elastomer material; The method for preparing the flexible composite material includes using an elastomer solution to composite a matrix with a biomass fiber membrane to obtain a molded body; The elastomer material includes waterborne polyurethane.

2. The flexible composite material according to claim 1, characterized in that, The thickness of the substrate is 0.1-0.6 mm; and / or, The biomass fiber membrane has a thickness of less than 0.1 mm and a density of 0.5 g / cm³. 3 the following.

3. The flexible composite material according to claim 2, characterized in that, The thickness of the substrate is 0.15-0.25 mm; and / or, The biomass fiber membrane has a thickness of 0.04-0.06 mm and a density of 0.34-0.37 g / cm³. 3 .

4. A method for preparing a flexible composite material according to any one of claims 1-3, characterized in that, include: The matrix and biomass fiber membrane are composited using an elastomer solution to obtain a molded body.

5. The preparation method according to claim 4, characterized in that, The method for preparing the biomass fiber membrane includes: dispersing biomass fibers in a solvent to obtain a slurry; and forming the slurry using a papermaking screen to obtain a biomass fiber membrane.

6. The preparation method according to claim 5, characterized in that, The biomass fiber in the slurry has a mass concentration of 0.05%-0.2%.

7. The preparation method according to claim 6, characterized in that, The biomass fiber in the slurry has a mass concentration of 0.05%-0.1%.

8. The preparation method according to claim 6 or 7, characterized in that, The dispersion process includes dispersion using a mixer.

9. The preparation method according to claim 8, characterized in that, The mixer rotates at 15,000-20,000 rpm, and the dispersion treatment takes 1-2 hours.

10. The preparation method according to any one of claims 4-7, characterized in that, The solid content of the elastomer solution is 28-34%; and / or, An elastomer solution is applied to cause the substrate to adhere to the biomass fiber membrane; the application method includes one or more combinations of spreading, coating, casting and spraying.

11. The preparation method according to any one of claims 4-7, characterized in that, The preparation method further includes a step of curing the molded body.

12. The preparation method according to claim 11, characterized in that, The curing temperature is 70-90℃, the curing time is 5-8 minutes, and the curing pressure is 0.5-2MPa.

Citation Information

Patent Citations

  • Preparation method and application of closed lignin-based waterborne polyurethane emulsion

    CN116239742A

  • Flexible microfiber bamboo-based composite material and preparation method thereof

    CN118893681A

  • Wood pulp air filter paper with nanofiber membrane

    CN208917597U